Using the TESOL Technology Standards Framework to evaluate students’ technological knowledge in an undergraduate Italian course - Xerou, Eftychia; Christoforou, Maria (My University, 2019)
The ubiquitous nature of technology has offered unprecedented opportunities for the learning experience. Various technological tools have become commonplace while many elaborate on the possibilities of authentic learning experiences created by immersive virtual applications. This reflective paper aims to evaluate how the integration of the TESOL (Teaching English to Speakers of other Languages) Technology Standards Framework can help align an Italian undergraduate course with the expected student learning outcomes in terms of technology. The students’ part of the TESOL Technology Standards Framework was used for this reflective evaluation. Each standard makes use of performance indicators that are reviewed and commented on. Furthermore, specific and general outcomes are supplemented in the Discussion and Conclusion section regarding the findings and the results of the overview. The course used for the purposes of this paper is Italian I, an A2-level elective course, offered at a public University. Italian I aims to develop students’ four skills: reading, writing, listening and speaking through contextualized learning, enhanced by innovative technological tools.
Keywords: TESOL technology standards framework; Italian language course; Student education; Technology